An Analysis of Violation and Flouting Maxim on Teacher-Students Interaction in English Teaching and Learning Process - Arofah, Siti; Mubarok, Husni (Language Circle: Journal of Language and Literature, 2021)
The objectives of this research are to analyze the type of violation and flouting the maxim of teacher-student interaction in the English teaching and learning process in MA Hasyim Asy’ari Bangsri and also find the most frequently produced between violation and flouting of the maxim. This research used the descriptive qualitative method. The data was obtained from the conversation between the teacher and students during the teaching and learning process and analyzed by categorizing utterances based on the violation and flouting maxim theory of the Cooperative Principle. The data were collected through the observation then analyzed by using the technique which is suggested by Miles and Huberman that consists of data reduction, data display, and drawing conclusion or data verification. The result of the research showed that there are four types of maxims that are violated by the teacher and students. These are the maxim of quantity 11 (50%), the maxim of quality 5 (22.73%), the maxim of relation 1 (4.54%), and the maxim of manner 5 (22.73%). The dominant violation was the maxim of quantity with 11 occurrences. Based on the findings, there are three types of flouting maxims in which the most of flouting maxim that is occurred was the maxim of relation. They are divided into 1 (14.29%) maxim of quantity, 2 (28.57%) maxim of quality, and 4 (57.14%) maxims of relation. In conclusion, the most produced between the violation and flouting was the violation of maxim with 22 (75.86%) of total occurrences. Meanwhile, the proportion of flouting maxim was 7 (24.14%).